Incremento de la delincuencia y la inseguridad en el Ecuador en el periodo 2021-2023 - Jaramillo Merino, Wilson Fernando (2024)
Every day the Ecuadorian population suffers the discomfort of not being able to carry out their normal activities due to the insecurity that has affected the country in recent years. This research aims to determine whether there was an increase in crime and insecurity in Ecuador in the period 2021-2023, through a mixed approach and a thorough analysis of the main data related to crime and insecurity. In this study it was determined that the increase in crime and insecurity occurs in all areas from 2021 to July 2023, with exponentially high values especially in the incomplete year 2023, likewise, in what has to do with the fulfillment of public policies implemented by the state and the measurement of their efficiency, the results confirm the low effectiveness of the same. It is therefore necessary that public policies be directed specially to strengthen state institutions and invest in training and equipping the security forces, as well as improving coordination between the different agencies responsible for public security.